2009
DOI: 10.1002/etc.56
|View full text |Cite|
|
Sign up to set email alerts
|

Aquatic toxicity of magnesium sulfate, and the influence of calcium, in very low ionic concentration water

Abstract: The toxicity of magnesium sulfate (MgSO(4)), and the influence of calcium (Ca), were assessed in very soft freshwater (natural Magela Creek water [NMCW]) using six freshwater species (Chlorella sp., Lemna aequinoctialis, Amerianna cumingi, Moinodaphnia macleayi, Hydra viridissima, and Mogurnda mogurnda). The study involved five stages: toxicity of MgSO(4) in NMCW, determination of the toxic ion, influence of Ca on Mg toxicity, toxicity of MgSO(4) at an Mg:Ca mass ratio of 9:1, and derivation of water quality g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 28 publications
9
109
2
Order By: Relevance
“…The possible metabolic cost of calcification in high (Mg/Ca)-WATER has been discussed by several workers (Xia et al, 1997b;De Deckker et al, 1999). Although it could be more energetically efficient to precipitate high magnesium calcite in high Mg/Ca solutions (Mucci and Morse, 1990), we have to take into account that Mg may be toxic to invertebrates (van Dam et al, 2010) and consequently there is a tradeoff between calcification and Mg excretion.…”
Section: Mg Uptake and Mg/camentioning
confidence: 97%
“…The possible metabolic cost of calcification in high (Mg/Ca)-WATER has been discussed by several workers (Xia et al, 1997b;De Deckker et al, 1999). Although it could be more energetically efficient to precipitate high magnesium calcite in high Mg/Ca solutions (Mucci and Morse, 1990), we have to take into account that Mg may be toxic to invertebrates (van Dam et al, 2010) and consequently there is a tradeoff between calcification and Mg excretion.…”
Section: Mg Uptake and Mg/camentioning
confidence: 97%
“…For example, based on population growth uranium was determined to be more toxic to H. viridissima at a pH of 6.6 than a pH of 8.6 (Hyne et al, 1992b). The toxicity of magnesium sulfate (MgSO 4 ), and the influence of calcium (Ca), were assessed in very soft freshwater where Ca was shown to have an ameliorative effect on Mg toxicity (van Dam et al, 2010). It was concluded that magnesium can be toxic at concentrations approaching natural background levels, but toxicity is dependent on Ca concentrations, with exposure in very low ionic concentration, Ca-deficient waters posing the greatest risk to aquatic life (van Dam et al, 2010).…”
Section: Fig 2 Evidence Of Biotransformation Of Xenobiotics In Hydrmentioning
confidence: 99%
“…The toxicity of magnesium sulfate (MgSO 4 ), and the influence of calcium (Ca), were assessed in very soft freshwater where Ca was shown to have an ameliorative effect on Mg toxicity (van Dam et al, 2010). It was concluded that magnesium can be toxic at concentrations approaching natural background levels, but toxicity is dependent on Ca concentrations, with exposure in very low ionic concentration, Ca-deficient waters posing the greatest risk to aquatic life (van Dam et al, 2010). Therefore, when comparing the toxicity of metals or the potential impact of metals on the environment, exposure conditions and abiotic factors should also be taken into account.…”
Section: Fig 2 Evidence Of Biotransformation Of Xenobiotics In Hydrmentioning
confidence: 99%
“…IC 10 and IC 50 , respectively) relative to the control responses. This particular model was used as it provided the best fit (r 2 ) to the data from a group of similar models.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 97%
“…Amerianna cumingi is also sensitive to 96-h exposure to manganese (Mn), with an IC10 of 340 µg L -1 [7], with only Hydra viridissima (IC10 = 140 µg L -1 ) and Hyalella azteca (IC10 = 96 µg L -1 ) being more sensitive [16]. Compared to other tropical freshwater species, A. cumingi was also the most sensitive to continuous magnesium exposure (Mg, IC10 = 5.6 mg L -1 ) [10], although it was found to be insensitive to pulses of Mg [8]. In part, its sensitivity could be attributed to it being a tropical species.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%